2013
DOI: 10.11646/phytotaxa.144.1.1
|View full text |Cite
|
Sign up to set email alerts
|

New combinations in Asiatic Oxybasis (Amaranthaceae s.l.): evidence from morphological, carpological and molecular data

Abstract: Two new combinations are proposed in Oxybasis (Chenopodioideae, Chenopodiaceae or Amaranthaceae s.l.). Chenopodium micranthum, described from Russia in the 1860s and known as C. urbicum subsp. sinicum in China, is assigned specific rank in Oxybasis. It appears to be widespread in China, Mongolia, Kazakhstan and Asiatic Russia. The Siberian-Mongolian C. gubanovii, recently described as a new species in Chenopodium sect. Pseudoblitum, is also assigned to Oxybasis. Molecular phylogenetic analysis using maximum li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“… nuttallianum ), is reduced to 1–2 leaves that may wither away completely by anthesis. From this study and from previous work ( Sukhorukov and Zhang 2013 ; Sukhorukov et al 2013 ; Sukhorukov 2014 ), it is evident that another character, the structure of the testa cells of the seed coat, is also diagnostic. In Oxybasis , as well as almost all other Chenopodieae , the seed testa cells have a reduced protoplast and “stalactites” hanging vertically in the outer wall (stalactite seed coat).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“… nuttallianum ), is reduced to 1–2 leaves that may wither away completely by anthesis. From this study and from previous work ( Sukhorukov and Zhang 2013 ; Sukhorukov et al 2013 ; Sukhorukov 2014 ), it is evident that another character, the structure of the testa cells of the seed coat, is also diagnostic. In Oxybasis , as well as almost all other Chenopodieae , the seed testa cells have a reduced protoplast and “stalactites” hanging vertically in the outer wall (stalactite seed coat).…”
Section: Discussionsupporting
confidence: 70%
“…Some of the most recent and drastic taxonomic changes have been proposed by Fuentes-Bazan et al (2012b) following their phylogenetic study of the large genus Chenopodium (~200–250 species) ( Fuentes-Bazan et al 2012a ) and this classification is currently accepted by many authors (e.g. Iamonico 2011 , 2014 ; Mosyakin 2013 ; Uotila 2017 ; Sukhorukov et al 2013 ; Sukhorukov and Kushunina 2014 , Hernández-Ledesma et al 2015 ; Mosyakin and Iamonico 2017 ). According to the findings by Fuentes-Bazan et al (2012b) , Chenopodium sensu lato was shown to be polyphyletic and members previously included in the genus are now placed in tribes Chenopodieae incl.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anatomy of the fruit and seed is important for the diagnostics and taxonomy of many Chenopodiaceae (for more see, e.g. Sukhorukov 2008, 2014, Sukhorukov and Zhang 2013, Sukhorukov et al 2013, 2014, 2015a). The fruit anatomy appears crucial to the diagnostics of many Corispermum and the fruits of almost all members were anatomically investigated in previous studies (Sukhorukov 2007a, 2007b, 2014, Sukhorukov et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The genus Oxybasis was resurrected to accomodate the Chenopodium species with branched stem, leaves not in basal rosette, inflorescence in not fleshy glomerules and usually dimorphic flowers with 3-5 tepals and horizontal and vertical seeds (Fuentes-Bazan et al 2012a, Sukhorukov 2013. Four European and Italian taxa Oxybasis chenopodioides and O. rubra represent a critical pair of species having fairly similar gross morphology, even though they do not seem to be close relatives (see e.g.…”
Section: Introductionmentioning
confidence: 99%